Cruising for cash: Prostitution on Grindr. (June 2017) - Brennan, Joseph
Highlights: Amateur use of gay geosocial app Grindr for paid sexual encounters. 600 comments from 22 relevant Reddit threads are selected for analysis. 3 key 'scripts' are identified from the discourse. From an individual seeking payment: 'cash strapped student', 'alternative to porn'. From a community responder perspective: 'naïve millennials'. Abstract: This article employs textual analysis in the cultural studies tradition to analyse Reddit discussion forums dedicated to the use of Grindr to solicit sex in exchange for cash, which is in violation of Grindr's terms of service. Of particular interest is a canvasing of the motivations behind amateur use of the app for paid sexual encounters. More than six hundred comments from twenty-two relevant threads are selected for analysis, drawn from the popular 'Gaybros' subreddit forum. I nominate three key 'scripts' from the discourse. Namely, from the perspective of the individual seeking payment: 'cash strapped student' and 'alternative to porn'; and 'naïve millennials' from a community responder perspective. These scripts offer insight into the profit-seeking motivations behind exploiting a popular sex-seeking tool, in particular by participants who would not otherwise engage in 'cruising for cash'. The discourse supports my view that the young men seeking payment conceive of themselves as mobile pornographers, a concept that embodies their willingness to exploit the affordances of mobile technology and the profits to be gained from youth and sex, without the digital traces of more traditional pornographic forms.